Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1063/1.1313552
|View full text |Cite
|
Sign up to set email alerts
|

The anisotropy of the small scale structure in high Reynolds number (Rλ∼1000) turbulent shear flow

Abstract: The postulate of local isotropy (PLI) is tested in a wind tunnel uniform shear flow in which the Reynolds number is varied over the range 100⩽Rλ⩽1, 100(6.7×102⩽Rl⩽6.3×104). The high Rλ is achieved by using an active grid [Mydlarski and Warhaft, J. Fluid Mech. 320, 331 (1996)] in conjunction with a shear generator. We focus on the increments of the longitudinal velocity fluctuations in the direction of the mean shear. PLI requires that odd order moments of these quantities approach zero as Rλ→∞. Confirming the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
231
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(261 citation statements)
references
References 38 publications
29
231
1
Order By: Relevance
“…The anisotropy is large at low Reynolds number and diminishes to a small value at R λ = 970. This observation tends to confirm recent experimental results which indicate that anisotropy may persist to much higher Reynolds numbers than previously believed [19,20].In summary, our measurements indicate that the Heisenberg-Yaglom scaling of acceleration variance is observed for 500 ≤ R λ ≤ 970. At lower Reynolds number, our measurements are consistent with the anomalous scaling observed in DNS [14,16].…”
supporting
confidence: 92%
“…The anisotropy is large at low Reynolds number and diminishes to a small value at R λ = 970. This observation tends to confirm recent experimental results which indicate that anisotropy may persist to much higher Reynolds numbers than previously believed [19,20].In summary, our measurements indicate that the Heisenberg-Yaglom scaling of acceleration variance is observed for 500 ≤ R λ ≤ 970. At lower Reynolds number, our measurements are consistent with the anomalous scaling observed in DNS [14,16].…”
supporting
confidence: 92%
“…Third-order transverse structure functions of the longitudinal velocity were found to have a scaling range, showing the existence of anisotropy at both inertial and dissipation scales. Shen & Warhaft [4] continued the experiments. They showed that the fifth moment of the derivative of the longitudinal fluctuation in the direction of the mean gradient, is of order 10 with no diminution with the Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time it was found that lateral structure functions D n (r) = <[u(x,y,z+r) -u(x,y,z)] n > of odd orders n = 3, 5, and 7 take non-zero values in the inertial range of lengths r (i.e., for TJ «r « L); hence the studied homogeneous-shear-flow turbulence is anisotropic also in the inertial range of lengths. Thus, results of [127] show that the shear-flow turbulence is locally non-isotropic, at least to Re x ~ 1000, and demonstrates no tendency to become isotropic at higher values of Re v Here again the question arises how the discovered local anisotropy can be combined with the validity of the ordinary laws of two and five thirds which was confirmed by data relating to very different high-Reynolds-number shear flows. Strong deviations from the predictions of K41 theory were in fact first detected in studies of small-scale fluctuations of temperature (or other passive scalars) in high-Reynolds-number turbulent flows.…”
Section: Concluding Remarks; Possible Role Of Navier-stokes Equationsmentioning
confidence: 69%
“…Their measurements in the atmospheric surface layer at 10 4 < Re x < 2xl0 4 led them to the conclusion that apparently in atmospheric turbulence there exists an inertial range where Eq. (17) is valid but its validity is often disturbed by velocity shear and finiteness of Re (see also the discussion of the results of the paper [127] below). However, the paper [122] did not clarify the origin of the similarity law (17).…”
Section: Kolmogorov's Theory Of Locally Isotropie Turbulencementioning
confidence: 99%
See 1 more Smart Citation